Sustainable cotton production through fertigation scheduling: A growth stage-based approach - Reethika, D; Baskar, K; Elayarajan, M; Bhakiyathu Saliha, B; Ravikumar, V; Manoharan, S (Plant Science Today, 2025)
Cotton cultivation in black soil regions faces challenges in optimizing nutrient use efficiency and maintaining soil health. This study was conducted to develop a fertigation schedule based on the crop growth nutrition curve for cotton to enhance sustainability. The suggested cultural practices are implemented and interventions comprised varying levels of recommended dose of fertilizers (RDF) through fertigation. Nutrients were supplied in stages: seedling stage (10 % NPK), vegetative stage (20 % NPK), square formation (30 % NPK), 50% flowering (20 % NPK) and boll formation and development stages (10 % NPK). The treatments included absolute control (T1) and various combinations of N, P and K at 75 %, 100 % and 125 % RDF levels (T2 to T8). Among all treatments, T8 (125 % potassium along with 100 % nitrogen and phosphorus), achieved the highest cotton yield. This suggests that increasing potassium levels through fertigation significantly enhances both crop productivity and soil health in black soils. These findings facilitate advancement of more effective fertigation methodologies that balance nutrient application with soil biological health, offering practical implications for sustainable cotton farming.